Mercury contamination in the recently described Brazilian white-tail dogfish Squalus albicaudus (Squalidae, Chondrichthyes). (July 2020) - Hauser-Davis, Rachel Ann; Pereira, Camila Ferreira; Pinto, Fernando; Torres, João Paulo M.; Malm, Olaf; Vianna, Marcelo
Abstract: The recently described Squalus albicaudus is a mesopredator shark and, as such, exposed to mercury biomagnification processes. Therefore, this study aimed to assess total Hg (THg) concentrations in S. albicaudus, a deep-water species, sampled off Southeastern Brazil and discuss ecological, reproductive, human consumption and conservation implications. Thirty-two individuals were sampled off the coast of Rio de Janeiro, including 13 gravid females carrying 34 embryos. Muscle THg concentrations were higher in all sex classes compared to liver, gonads and brain. The last three, in turn, presented THg concentrations above toxic biota thresholds. Significant correlations were observed between muscle and brain and liver, indicating systemic Hg contamination and inter-organ transport and distribution. In addition, correlations observed between organs strongly support efficient Hg blood-brain barrier crossing and maternal transfer. Maternal THg transfer was observed, with embryo THg also above toxic thresholds for fish. THg levels in muscle and liver, as well as embryos, were higher compared to other Squalus species worldwide. Hg contamination off the coast of Rio de Janeiro is of significant concern and should be further assessed. Potential human consumption risks are noted, as muscle THg concentrations were above maximum permissible levels set by regulatory agencies. Graphical abstract: Image 1048 Highlights: This study reports the first ecotoxicological report for S. albicaudus . Total Hg in 32 specimens sampled off the coast of Rio de Janeiro were determined. Hg levels in muscle, liver, gonads and brain were above toxic thresholds for fish. Maternal THg offloading was noted, and embryo Hg was above toxic thresholds for fish. THg in males and embryos were higher compared to other Squalus species worldwide.